Justicia radical : una interpretación psicoanalítica de las postdictaduras en España y el Cono Sur - Martín-Cabrera, Luis, 1972- (Memoria rota. Exilios y heterodoxias. Estudios, 2016)
This work investigates the convoluted relationship between memory and justice in Spain and the Southern Cone as it is portrayed in political documentaries and detective fiction from Spain and the Southern Cone.